Food safety and informal markets: Animal products in sub-Saharan Africa - Roesel, Kristina; Grace, Delia (Routledge, 2014)
Animal products are vital components of the diets and livelihoods of people across sub-Saharan Africa. They are frequently traded in local, unregulated markets and this can pose significant health risks. This volume presents an accessible overview of these issues in the context of food safety, zoonoses and public health, while at the same time maintaining fair and equitable livelihoods for poorer people across the continent. The book includes a review of the key issues and 25 case studies of the meat, milk, egg and fish food sectors drawn from a wide range of countries in East, West and Southern Africa, as part of the "Safe Food, Fair Food" project. It describes a realistic analysis of food safety risk by developing a methodology of ‘participatory food safety risk assessment’, involving small-scale producers and consumers in the process of data collection in a data-poor environment often found in developing countries. This approach aims to ensure market access for poor producers, while adopting a realistic and pragmatic strategy for reducing the risk of food-borne diseases for consumers.